Microbiological survey of ready-to-eat foods and associated preparation surfaces in cafeterias of public sector universities. Issue 1 (1st January 2021) - Giwa, Abdulmoseen Segun; Memon, Abdul Ghaffar; Ahmed Shaikh, Asif; Korai, Rashid; Maitlo, Ghulam Ullah; Maitlo, Inamullah; Ali, Safdar; Ahmad, Jabran
ABSTRACT: A microbiological and sanitation survey of ready-to-eat (RTE) food samples, cutlery, utensils, and hands of food handlers, food preparation surfaces, serving counters, washing areas, and refrigerator handles were conducted. The samples were collected using environmental swabs, and these samples were analyzed using standard plating techniques. Samples were characterized after aerobic plate counts (APC) and isolated for mesophilic aerobic bacteria (MAB), total coliforms, Staphylococcus aureus, Escherichia coli., Salmonella spp., Shigella spp., Pseudomonas spp., Enterobacter spp., Klebsiella spp ., and yeast. This study suggested that good-hygiene practices can minimize bacterial counts, thereby decreasing the reservoirs for bacterial contamination. It also improves the hygienic condition of RTE-foods in the cafeteria of Universities.